Will Hybrid Meetings Replace Face-To-Face Meetings Post COVID-19 Era? Perceptions and Views From The Urological Community - TANIDIR, YILÖREN (ELSEVIER SCIENCE INC, 2021)
OBJECTIVE To understand the preference and role of 'hybrid' urological meetings compared to face-to-face and online meetings during and after COVID-19 pandemic. The secondary outcome was finding out the most preferable webinar setting. METHODS An online global survey was done between June 06 and July 05, 2020, using SurveyMonkey. The target participants were urology healthcare providers. The survey was disseminated via mailing lists and the Twitter platform. RESULTS A total of 526 urology providers from 56 countries responded to the survey and it was completed by 73.3%. Participants' overall experience was better in a face-to-face meeting, followed by a hybrid and webinar only meeting. While opportunities for networking was identified as high in face-to-face meeting, online webinars were more cost effective, and learning opportunity and reach of audience was higher for hybrid meetings. For online webinar format, Zoom platform was used by 73% and majority (69%) saw it on their laptop or desktop. The preference was for a 1-hour webinar in the evenings with 3-5 speakers. Urology residents rated face-to-face meetings to have better cost-effectiveness when compared to consultants. Post COVID-19, more than half of all respondents would prefer hybrid meetings compared to the other formats. CONCLUSION While there will be a place for face-to-face meetings, COVID-19 situation has led to a preference towards hybrid meetings which is ideal for a global reach in the future. It is plausible that most urological associations will move towards a hybrid model for their meetings. (C) 2021 Elsevier Inc.
Keywords: WEBINAR; ONLINE